Cupping therapy and nursing management for a patient with lumbosacral pain caused by sequelae of pelvic inflammatory disease (拔罐疗法治疗1例盆腔炎性疾病后遗症腰骶疼痛的护理体会) - ZHANG Rao (张绕); LU Ying (卢英); LIU Xiaoyu (刘晓宇); WANG Xujing (王雪静); SHEN Yueyue (申月月) (中西医结合护理)
This paper reviewed the cupping therapy and nursing management for a patient of lumbosacral pain caused by sequelae of pelvic inflammatory disease (SPID). It mainly included the operation method and precautions of cupping therapy, nursing evaluation, condition observation, psychological care, diet guidance and other interventions. Based on acupoint selection by syndrome differentiation, cupping therapy was carried out to relieve the lumbosacral pain caused by SPID. (本文总结1例拔罐疗法治疗盆腔炎性疾病后遗症所致腰骶疼痛的护理经验, 主要包括拔罐疗法的操作方法和注意事项以及相关护理评估、病情观察、心理护理及饮食指导等护理措施。通过辨证选穴, 实施拔罐技术, 有助于缓解患者腰骶疼痛。)